Agronomic characteristics and genetic relationship of putative transgenic rice lines of cv. Fatmawati with the Glu-1Dx5 transgene (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Carsono N, Prayoga GI, Sari S, Rachmadi M. 2021. Agronomic characteristics and genetic relationship of putative transgenic rice lines of cv. Fatmawati with the Glu-1Dx5 transgene. Biodiversitas 23: 291-298. Transgenic rice lines cv. Fatmawati with the Glu-1Dx5 transgene (encoding high molecular weight glutenin sub-unit Dx5 from bread wheat) has been produced in order to improve dough functionality of rice flour. These lines have reached T1 (transformant-1) dan T2 (transformant-2) generations. Some transgenic rice plants obtained from in vitro culture and transformation events frequently show phenotypic and genotypic variations from the original plants, thus evaluation of agronomic traits of these transgenic rice is highly important in order to obtain rice genotypes with the best agronomic traits that will be integrated into rice breeding program. Nine transgenic rice lines and two check lines, i.e. seed-derived and callus-derived rice lines, were used in this experiment. A comparison between transgenic rice traits with those of non-transgenic checks was done by student’s t-test and relationship among transgenic rice lines was evaluated by UPGMA (Unweighted Pair Group Method with Mean Arithmetic) method using NT Sys (Numerical Taxonomy and Multivariate Analysis System). Results indicated that agronomic traits of transgenic rice lines were similar to those of non-transgenic check except for number of productive tillers (T2-11, T2-12, T2-20), the maximum number of tillers (T2-7, T2-11, T2-12, T2-20), number of filled grains (T1-45) and days to maturity (all T2 lines). It suggests that somaclonal variations, gene insertional effect, genetic and epigenetic mutations might occur. Genetic relationship between putative transgenic and non-transgenic checks was closely related, although somaclonal variants were found. The selected transgenic rice lines will be incorporated into rice breeding programs.
Keywords: Callus-derived plants, Somaclonal variation, Transformation effect, Transgenic rice